2011
DOI: 10.1182/blood-2010-09-306019
|View full text |Cite
|
Sign up to set email alerts
|

B cells lacking the tumor suppressor TNFAIP3/A20 display impaired differentiation and hyperactivation and cause inflammation and autoimmunity in aged mice

Abstract: IntroductionB cells play essential roles during protective immune responses to invading pathogens. On encounter of foreign antigen and with cognate T-cell help, B lymphocytes proliferate and form distinct histologic structures, termed germinal center (GC). In the GC, they undergo somatic hypermutation and class-switch recombination. During somatic hypermutation, they introduce random mutations into their immunoglobulin variable regions while they exchange the heavy chain constant region during class-switch rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
153
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 166 publications
(163 citation statements)
references
References 44 publications
4
153
2
Order By: Relevance
“…In this study, we found that there was only a minor increase in total B cell numbers, whereas myeloid cells and T cells increased significantly in the enlarged spleens in 8-wk-old mice. The similar phenomenon, which is that the expanded myeloid cells and T cells are induced in reaction to autoimmunity and inflammation, was found in mice lacking genes involved in NF-kB activation (45)(46)(47). Previously, NF-kB was also reported to be regulated by other PRMTs (48)(49)(50), suggesting that arginine methylation plays unique roles in NF-kB activation.…”
Section: Discussionsupporting
confidence: 60%
“…In this study, we found that there was only a minor increase in total B cell numbers, whereas myeloid cells and T cells increased significantly in the enlarged spleens in 8-wk-old mice. The similar phenomenon, which is that the expanded myeloid cells and T cells are induced in reaction to autoimmunity and inflammation, was found in mice lacking genes involved in NF-kB activation (45)(46)(47). Previously, NF-kB was also reported to be regulated by other PRMTs (48)(49)(50), suggesting that arginine methylation plays unique roles in NF-kB activation.…”
Section: Discussionsupporting
confidence: 60%
“…Mutations in B cells were previously shown to also affect other immune cells such as T cells, as shown with mice that lack A20 in B cells [25,26]. Except for memory T cells, which were increased in total cell numbers (Supporting Information Fig.…”
Section: Selective Emergence Of B-1 and Memory B Cells In Secondary Lmentioning
confidence: 79%
“…3I). This effect might indicate a survival advantage of GC B cells in NIK BKO mice, as seen for B-1, or that these cells escaped Cre-mediated deletion more efficiently compared to other B cells.Mutations in B cells were previously shown to also affect other immune cells such as T cells, as shown with mice that lack A20 in B cells [25,26]. Except for memory T cells, which were increased in total cell numbers (Supporting Information Fig.…”
mentioning
confidence: 79%
“…Cell type-specific deletion of A20 in immune cells and other tissues like intestinal epithelial cells and skin further confirmed its crucial role in the maintenance of tissue homeostasis and to prevent inflammatory diseases including autoimmunity (9)(10)(11)(12)(13)(14)(15). In B cells, loss of A20 causes hyperreactivity, general immune activation, and the production of autoantibodies (10,11,16).…”
mentioning
confidence: 80%
“…All mouse strains employed in this study are published and were originally generated using C57BL/6 embryonic stem cells or backcrossed to C57BL/6 at least six times (11,32). Mice were housed in a specific pathogen-free environment in the animal facility of the Max Planck Institute of Biochemistry, Martinsried, Germany, and all animal procedures were approved by the Regierung of Oberbayern.…”
Section: Micementioning
confidence: 99%